XI International Meeting of Phytosociology - Natural and semi-natural habitats of the Natura 2000 Network: Improving knowledge to support conservation measures - Quinto-Canas, Ricardo (2020)
Livro de resumos do XI International Meeting of Phytosociology - Natural and semi-natural habitats of the Natura 2000 Network, que decorreu em Faro em Setembro de 2019